2015
DOI: 10.1016/j.cub.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Expansion of Domain Archaea Highlights Roles for Organisms from New Phyla in Anaerobic Carbon Cycling

Abstract: The results dramatically expand genomic sampling of the domain Archaea and clarify taxonomic designations within a major superphylum. This study, in combination with recently published work on bacterial phyla lacking cultivated representatives, reveals a fascinating phenomenon of major radiations of organisms with small genomes, novel proteome composition, and strong interdependence in both domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
621
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(660 citation statements)
references
References 60 publications
(94 reference statements)
34
621
0
5
Order By: Relevance
“…These include elucidation of several phyla previously lacking genomic representatives [27][28][29] , including the Patescibacteria superphylum 4 , which has subsequently been referred to as the 'Candidate Phyla Radiation' (CPR) as it may consist of upwards of 35 candidate phyla 10,30 . Notable evolutionary and metabolic insights include the discovery of eukaryotic-like cytoskeleton genes in the archaeon Lokiarchaeota 31,32 and the identification of putative methane-metabolizing genes in the Bathyarchaeota and Verstraetearchaeota phyla 33,34 .…”
mentioning
confidence: 99%
“…These include elucidation of several phyla previously lacking genomic representatives [27][28][29] , including the Patescibacteria superphylum 4 , which has subsequently been referred to as the 'Candidate Phyla Radiation' (CPR) as it may consist of upwards of 35 candidate phyla 10,30 . Notable evolutionary and metabolic insights include the discovery of eukaryotic-like cytoskeleton genes in the archaeon Lokiarchaeota 31,32 and the identification of putative methane-metabolizing genes in the Bathyarchaeota and Verstraetearchaeota phyla 33,34 .…”
mentioning
confidence: 99%
“…Many of the DPANN Archaea described to date have small cells (<1 μm) (5) and reduced genomes in which many core metabolic pathways are incomplete (5). The first DPANN to be characterized, Nanoarchaeum equitans, is obligately dependent on the crenarchaeote Ignicoccus hospitalis for growth (33), and other members of the group also have been observed in direct contact with larger archaeal cells (34), suggesting that symbiotic or parasitic lifestyles may be a common feature of the DPANN lineage.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the classically defined Euryarchaeota and Crenarchaeota (1), the scope of archaeal diversity has been dramatically expanded in recent years by the discovery of major new lineages using traditional and molecular methods. These lineages are of major ecological and evolutionary significance and include the Thaumarchaeota (2, 3), ammonia oxidizers found in soils and the open ocean, where they play a critical role in the global nitrogen cycle (3); the DPANN (Diapherotrites, Parvarchaeota, Aenigmarchaeota, Nanoarchaeota, Nanohaloarchaea) Archaea, a diverse group with small cells and genomes, whose reduced metabolic repertoires suggest that they may be symbionts or parasites of other prokaryotes (4,5); and the "Asgard" Archaea, the closest archaeal relatives of eukaryotes described to date (6,7), whose phylogenetic position and gene content are key to ongoing debates about eukaryote origins. In recent years, phylogenetic analyses have supported a clade uniting the Thaumarchaeota, Crenarchaeota, Aigarchaeota, and Korarchaeota that has been informally named the "TACK" Archaea (8) or "Proteoarchaeota" (9).…”
mentioning
confidence: 99%
“…The latter archaeal group, the seventh order of methanogens, are methylotrophic methanogens obtaining energy and carbon from methanol and methylated amines (Paul et al, 2012;Dridi et al, 2012;Iino et al, 2013;Borrel et al, 2014). Although no information on the potential metabolism of the Terrestrial Miscellaneous Euryarchaeotal Group group is available, recent findings from metagenomic data (Meng et al, 2014;Castelle et al, 2015) and single-cell genomics (Lloyd et al, 2013) suggested that members of the MCG and Marine Benthic Group D lineages may be involved in the degradation of detrital proteins both in marine and continental sediments. The high PD of the MCG lineage invalidates any general assumption of potential metabolisms shared between all MCG subgroups (the specialization of certain subgroups towards freshwater and marine habitats is a good example of this).…”
Section: Evolutionary Relationships Between Freshwater and Marine Mcgmentioning
confidence: 99%